Islam in the Nordic and Baltic Countries (Islamic Studies Series): By Göran Larsson, ed. (Oxon, UK and New York: Routledge, 2009. hbk. 147 pages) (American Journal of Islam and Society, 2011)
Until recently, scholarly writing on Islam in the Nordic and Baltic regionshas proved to be a woefully scant enterprise. Most works that have emergedon the topic of Islam in Europe focus on the United Kingdom and France,leaving northern and eastern European regions largely underanalyzed. It isin this respect that Göran Larssonʼs edited volume is to be welcomed as animportant and long overdue contribution to the topic ...